Language, Data and Knowledge 2023 (LDK 2023): proceedings of the 4th Conference on Language, Data and Knowledge - Carvalho, Sara; Fahad Khan, Anas; Ostroški Anić, Ana; Spahiu, Blerina; Gracia, Jorge; McCrae, John P.; Gromann, Dagmar; Heinisch, Barbara; Salgado, Ana (NOVA FCSH - CLUNL, 2023)
This volume presents the proceedings of the 4th Conference on Language, Data and Knowledge held in Vienna, Austria, from 12-15 September 2023. Language, Data and Knowledge (LDK) is a biennial conference series on matters of human language technology, data science, and knowledge representation. This fourth edition of the LDK conference is hosted by the University of Vienna in Vienna, Austria. Significant support was provided by the NexusLinguarum COST Action CA18209, “European network for Web-centred linguistic data science”, and by the following sponsors: the Coreon team and the Vienna Convention Bureau, as a department of the Vienna Tourist Board.
Gesehen am 14.12.2023
Keywords: Konferenzschrift